PROFIL PELAJAR PANCASILA INTEGRASI DENGAN PENDIDIKAN AGAMA ISLAM - Anwar, Ahmad; Sariman, Sariman; Muchlisin, Imam (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
The Pancasila student profile is a depiction of the characteristics of graduates that are intended to be developed through the education system. This research employs qualitative descriptive and library research methods, drawing data from various sources such as readings, books, articles, and other references. The findings reveal that the Pancasila student profile consists of six main dimensions: a) belief in and devotion to the One Almighty God and noble conduct, b) independence, c) mutual cooperation, d) global diversity, e) critical thinking, and f) creativity. These dimensions are closely intertwined with the values of Islamic Education, as evidenced by numerous Quranic verses discussing each dimension. This underscores Islam's relevance in addressing contemporary challenges. Therefore, it is crucial for Islamic Education teachers to actively contribute to realizing these six Pancasila student profiles, aiming to cultivate a generation strong in faith and noble character.